Pendampingan Analisis Kelayakan Sosial Pasar Tradisional Landungsari: Assistance for Social Feasibility Analysis of Landungsari Tradisional Markets - Sulistyowati, Tutik; Susilo, Rachmad Kristiono Dwi; Prismadani, Zikri; Sabilillah, Abdul Aziz; Mawarid, Ahmad Farhan; Fuadi, Farhan; Wahyudi, Oky Firman; Az-Zahro, Divanda Nilam (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The market is a collection of all buyers and sellers interacting socially in selling and purchasing goods. The existence of markets, especially traditional markets, supports economic activities that can contribute to the economic growth of the surrounding community. The traditional market is the center of buying and selling transactions directly in the community. One of its functions is as a center for the socio-economic activities of the local community. The traditional market of Landungsari Village is an economic forum for the Landungsari community in buying and selling transactions between buyers and sellers. Market development must adjust to the development of the surrounding community. The problem in the traditional market of Landungsari Village is that there is no social feasibility study in developing and realigning the Landungsari Market in the surrounding community. The service aims to solve the problems by conducting a social feasibility study survey of the development and improvement plan and realignment of the Landungsari Market. In its implementation, the service team partnered with the Landungsari Market Manager and the Landungsari Village Government. The result of the service was that 76% of the subjects expected an improvement in the cleanliness of the Landungsari Market, and 100% of the subjects also expected the provision of evacuation routes, symbols, and disaster mitigation tools.